2021
DOI: 10.3389/fendo.2021.766516
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Serum Cystatin C and Thyroid Diseases: A Systematic Review and Meta-Analysis

Abstract: BackgroundCystatin C (CysC) is often used to diagnose and monitor renal diseases. Although some studies have investigated the association between serum CysC levels and thyroid diseases, their reported results were inconsistent. Therefore, the relationship between CysC levels and thyroid diseases remains controversial.AimThis meta-analysis aimed to statistically evaluate serum CysC levels in patients with thyroid diseases.MethodsA literature search was conducted using the PubMed, Web of Science, Embase, EBSCO, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
0
10
0
1
Order By: Relevance
“…There were several limitations in our study, with one attributed to not assessing thyroid function (16,42,43). A meta-analysis evaluating serum CysC levels in 1265 patients with thyroid disease and 894 controls revealed higher CysC levels among hyperthyroid subjects compared to lower CysC values in those with hypothyroidism.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…There were several limitations in our study, with one attributed to not assessing thyroid function (16,42,43). A meta-analysis evaluating serum CysC levels in 1265 patients with thyroid disease and 894 controls revealed higher CysC levels among hyperthyroid subjects compared to lower CysC values in those with hypothyroidism.…”
Section: Discussionmentioning
confidence: 92%
“…A meta-analysis evaluating serum CysC levels in 1265 patients with thyroid disease and 894 controls revealed higher CysC levels among hyperthyroid subjects compared to lower CysC values in those with hypothyroidism. Furthermore, with treatment of the thyroid disease, CysC levels were notably affected and therefore, the study concluded that serum CysC could be a marker for monitoring thyroid disease (43). Another limitation of our study was the small sample of 45 patients that only included those who underwent a protocol biopsy in the rst 2 years post-transplant, or a for-cause biopsy, which may have introduced selection bias.…”
Section: Discussionmentioning
confidence: 96%
“…However, the underlying mechanisms are not clear, and uncertainties prevail regarding the role of thyroid function and thyroid autoimmunity. More recent studies have pointed toward a specific association between autoimmune hypothyroidism and increased levels of CysC ( 8 , 9 ), which contrasts the general hypothesis that lack of thyroid hormones reduces levels of CysC ( 7 , 10 ). With a focus on immunological mechanisms, another thought is on the interaction with the physiological immune suppression seen in a normal pregnancy ( 11 ).…”
Section: Introductionmentioning
confidence: 84%
“…On the other hand, no thyroid-healthy control group was investigated. Gathering of 11 studies up until 2019 in a meta-analysis led to the conclusion that hyperthyroidism associates with higher levels of CysC whereas hypothyroidism associates with lower levels ( 10 ). However, the studies included showed considerable heterogeneity and small sample sizes, which led the authors to interpret with caution and call for further studies ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation